Dairy Business Analysis Project: 2006 Financial Summary - Albert De Vries; Russell Giesy; Lane Ely; Mary Sowerby; Brent Broaddus; Chris Vann (EDIS)
AN196, a 13-page illustrated report by A. De Vries, R. Giesy, L. Ely, M. Sowerby, B. Broaddus, and C. Vann, summarizes the financial performance of 22 dairy farms that participated in a 2006 survey. It is intended for general use by dairy farmers, the allied industry, government, and educational professionals. Published by the UF Department of Animal Science, March 2008.